2022
DOI: 10.1055/s-0042-1743238
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Benefits of Information Communication Technologies Used by Health Care Aides

Abstract: Background Although information and communication technologies (ICT) are becoming more common among health care providers, there is little evidence on how ICT can support health care aides. Health care aides, also known as personal care workers, are unlicensed service providers who encompass the second largest workforce, next to nurses, that provide care to older adults in Canada. Objective The purpose of this literature review is to examine the range and extent of barriers and benefits of ICT used b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 116 publications
(323 reference statements)
0
9
0
Order By: Relevance
“…[29][30][31][32][33] Family caregivers of individuals living in LTC may be reluctant to contact staff to inquire about the status of their relatives because of the high workloads experienced by the LTC staff. 9,13,34 Mobile technologies, including smartphone applications, can facilitate communication with staff, 5,[35][36][37][38][39][40] by supporting care coordination and remote care. 6,[41][42][43][44] Mobile technologies can also enhance social interactions with the care recipient and increase the engagement of families in care activities.…”
Section: Background and Significancementioning
confidence: 99%
“…[29][30][31][32][33] Family caregivers of individuals living in LTC may be reluctant to contact staff to inquire about the status of their relatives because of the high workloads experienced by the LTC staff. 9,13,34 Mobile technologies, including smartphone applications, can facilitate communication with staff, 5,[35][36][37][38][39][40] by supporting care coordination and remote care. 6,[41][42][43][44] Mobile technologies can also enhance social interactions with the care recipient and increase the engagement of families in care activities.…”
Section: Background and Significancementioning
confidence: 99%
“…Knowledge of the usability and acceptance ICTs in health care settings is imperative for the success of ICT deployment. Perez et al [ 10 ] recently identified the drawbacks and benefits of ICT adoption by health care aides. A major deterrent is the cumbersome and time-consuming nature of the adoption and implementation of ICTs.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the COVID-19 pandemic, an understanding of user-technology interactions is fundamental to ICT design and deployment in care settings. Health care aides, nurse managers, and other health care providers benefit from ICT use through improved communication, workflow support, and information accessibility [ 10 , 14 ]. Furthermore, there is an opportunity to enhance communication between clients and their family members [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study using the Internet and a telehealth care system to strengthen interactions between the community, hospital staff, and family members through virtual video, telephone, and visitor management can effectively improve family members' satisfaction and reduce patient transfer costs and length of hospitalization. 11 Several medical institutions in Taiwan have implemented telehealth care systems, allowing older and chronic patients to monitor physiological information at home and within the community to understand their health status and prevent disease. In addition, such systems can aid caregivers or family members in improving the quality of care for older adults.…”
Section: Introductionmentioning
confidence: 99%